ANTESEDEN RETURN ON ASSET (ROA) PADA BANK BUMN INDONESIA - Andi Tenriola (BJRM (Bongaya Journal of Research in Management), 2019)
This study aims to examine and analyze the effect of Capital Adequacy Ratio (CAR),Operating Expenses and Cost Efficiency (BOPO) and Loan to Deposit Ratio (LDR) to Return onassets (ROA). Return on assets (ROA) or profitability is one indicator that can be used to measurebank performance. The population used in this study is state-owned banks registered with BankIndonesia during the 2014-2018 period. In this study the sampling technique used total samplingtechniques using quarterly financial statements owned (1) PT. BNI (Persero), Tbk (2) Bank BRI(Persero), Tbk, (3) PT Bank Mandiri (Persero), Tbk; and (4) PT Bank BTN (Persero) so that with thesample, the number of samples in this study were (4 Quarter x 5 Years of Observation x 4 BUMNBanks = 80 panel data units). The results of multiple regression analysis provide evidence that CARhas a significant positive effect on ROA. Operational efficiency and cost efficiency (BOPO) has asignificant negative effect on return on assets (ROA). LDR has a significant negative effect on ROA.For the biggest contribution proven in CAR, that CAR has a dominant effect on ROA.